Estimating Hull Resistance of a Pontoon by using CFD - Ngo, He Van; Hoang, Cong Liem; Ngo, Van Hien (Vietnam Journal of Marine Science and Technology, 2022)
This paper presents our estimated results of hull resistance acting on a full-scale pontoon by a commercial Computational Fluid Dynamic (CFD). The results have been compared with those obtained by using various well-established valuable empirical formulae introduced by the International Towing Tank Conference (ITTC). The differences between the empirical formulae and the CFD results have been found and discussed.